THE USAGE OF ONOMATOPOEIA SOUND SYMBOL ON BOOK “DIARY OF A WIMPY KID” - Alfia Tawaffani Muslima (Universitas Muhammadiyah Semarang, 2021)
The aim of the research is to know the ussage several of phonetic sign on a language, like onomatopoeia, phonesthemes and ideopone on the book